2013
DOI: 10.1177/8755123313502342
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Early-career School Music Teachers Regarding Their Preservice Preparation

Abstract: The purpose of the present study was to examine the perceptions of early-career music teachers regarding their preservice music education program, with respect to its success in developing competencies needed to be effective in school music classrooms. An online survey was completed by 101 school music teachers designed to elicit responses related to the following questions: (a) What are early-career music teachers' perceptions of their preparation for teaching in school music classrooms? (b) What aspects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 19 publications
3
30
0
6
Order By: Relevance
“…The comments promoting the value of field experiences and mentorships support findings by Brophy (2002) and Legette (2013) who also found that music education students desired more effective field experiences with quality teachers. These findings, in consideration of Taylor's (1970) counterpoint that decontextualized field experiences lacked value, may suggest that field experiences could be incorporated into existing courses.…”
Section: Discussionsupporting
confidence: 74%
“…The comments promoting the value of field experiences and mentorships support findings by Brophy (2002) and Legette (2013) who also found that music education students desired more effective field experiences with quality teachers. These findings, in consideration of Taylor's (1970) counterpoint that decontextualized field experiences lacked value, may suggest that field experiences could be incorporated into existing courses.…”
Section: Discussionsupporting
confidence: 74%
“…This study examined the perceptions of music teachers specifically, as it has been consistently argued that the experiences of early career music teachers are characterized by practical challenges associated with teaching the discipline area (Krueger, 2001;Scheib, 2006;Ballantyne, 2007;Conway, 2012;Legette, 2013). This is implicated in the findings by Buonomo et al (2017), who argue that the contextual stressors provided by teaching roles which require extracurricular responsibilities and workload (like music teachers) are at greater risk of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences in real classrooms are considered a critical part of music teacher preparation, and various hands-on teaching activities are thought to allow students to make connections between theory and practice in real time and in authentic contexts. Research has shown that practicing teachers rate fieldwork as one of the most valuable parts of teacher preparation and also recommend more of these authentic field-teaching activities (Brophy, 2002;Conway, 2002Conway, , 2012Groulx, 2016;Legette, 2013;Roulston, Legette, & Womack, 2005). Teachers also have consistently recommended broader approaches to the preservice music education curriculum incorporating more "detracked" experiences outside of the chosen music specialization (Conway, 2002;2012;Groulx, 2016).…”
mentioning
confidence: 99%